Requests for support by pregnant women with eating disorder symptoms: a systematic literature review of qualitative studies - Cecilia Brundin Pettersson; Klara Lundvik; Martina Isaksson; Mia Ramklint (Journal of Eating Disorders)
Abstract Background During the peripartum period, four to 13 percent of women may be affected by eating disorders (ED). Previous reviews of qualitative studies in pregnant women with ED have mainly focused on the women’s experiences during pregnancy and not on their expressed needs. This systematic review aimed to identify which types of support were requested by pregnant women with ED. Methods The review was conducted in accordance with the “Enhancing transparency in reporting the synthesis of qualitative research” (ENTREQ) guidelines. Search for studies published between 1/1 2011- 14/3 2023 and 14/3 2023–9/1 2025, were performed in the following databases: PubMed, CINAHL, PsycInfo and Scopus. Studies were included if (1) the study population was pregnant women with ED symptoms /ED/ problems with food and eating, and (2) the study was an original qualitative study, and (3) the article was written in English. Rayyan, the AI-powered tool for systematic reviews, was used. Inclusion criteria were based on the SPICE-format. The CASP tool was used to assess quality in the included studies. Selected studies were read and critically appraised by two independent reviewers and a descriptive synthesis was conducted of expressed wishes for support based on quotes from the included studies. This review was preregistered in Prospero, 1/9 2023, (CRD42023456326). Results Of 992 studies, only five fulfilled the inclusion criteria. From these studies three themes emerged: wish for support from health care, wish to get support from a partner and wish to use self-help strategies. Conclusion This review found a knowledge gap regarding the type of support requested by pregnant women with ED symptoms. Plain English summary In this study, we aimed to explore the existing literature on the needs of support expressed by pregnant women with eating disorders. We reviewed studies published between 2011 and 2025, and found only five that partially addressed these needs. Three main themes emerged: wish for support, self-help strategies, and support from a partner. Our findings showed that the women expressed a desire for their midwives to have enough knowledge about eating disorders to bring up the topic and talk about it with them. We also identified a gap in the literature, highlight the need for more qualitative research to better understand the specific support these women want and need during pregnancy. The role of the partner in providing support should also be addressed in future research.